Social protection, food security, and asset formation - Hidrobo, Melissa; Hoddinott, John F.; Kumar, Neha; Olivier, Meghan (Elsevier, 2018)
The last two decades have seen a rapid rise in social protection programs and studies that assess their impacts on a large number of domains. We construct a new database of studies of these programs that report impacts on food security outcomes and asset formation. Our meta-analysis finds that social protection programs improve both the quantity and quality of food consumed by beneficiaries. The magnitudes of these effect sizes are meaningful. The average social protection program increases the value of food consumed/expenditure by 13% and caloric acquisition by 8%. Food expenditure rises faster than caloric acquisition because households use transfers to improve the quality of their diet, most notably increasing their consumption of calories from animal source foods. Since the consumption of animal source foods in these populations is low, and because there are significant nutritional benefits to increasing the consumption of these, this is a positive outcome. Our meta-analysis also finds that social protection programs lead to increased asset holdings as measured by livestock, non-farm productive assets, farm productive assets, and savings. There is no impact on land holdings though the number of studies that assess these is small.